2010
DOI: 10.1007/s10389-010-0371-5
|View full text |Cite
|
Sign up to set email alerts
|

Physical capacity in physically active and non-active adolescents

Abstract: Aim: The aim of this study was to investigate differences in physical capacity between physically active and non-active men and women among graduates from upper secondary school. Subject and methods: Research participants were graduates (38 women and 61 men) from upper secondary school. Physical activity was determined using the International Physical Activity Questionnaire, and participants were dichotomously characterized as being physically active or physically non-active according to the recommendations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
1
0
0
Order By: Relevance
“…The results demonstrated that there were no significant differences in grip strength results between activity groups. This observation is in accord with the findings of previous studies conducted with children [ 38 ], young adults [ 39 ], and older adults [ 40 ]. Furthermore, no significant associations were obtained between PAL and grip strength values in both genders.…”
Section: Discussionsupporting
confidence: 93%
“…The results demonstrated that there were no significant differences in grip strength results between activity groups. This observation is in accord with the findings of previous studies conducted with children [ 38 ], young adults [ 39 ], and older adults [ 40 ]. Furthermore, no significant associations were obtained between PAL and grip strength values in both genders.…”
Section: Discussionsupporting
confidence: 93%